Impacts of US tariffs on global agricultural trade flows - Glauber, Joseph W.; Piñeiro, Valeria; Gianatiempo, Juan Pablo (2026)
Since his return to the White House in January 2025, Donald Trump has, in a few short months, upended the global trading system with a series of tariff announcements that threaten trade and have created much uncertainty in global markets. Citing the persistent US trade deficit and what he considers unfair practices by other countries, the president declared April 2 “Liberation Day” and announced a sweeping new set of supplemental tariffs on imports from nearly all major US trading partners. This announcement followed a series of previous actions taken since the beginning of the administration, including 20% tariffs on Chinese imports, 25% tariffs on automobiles and auto parts, and duties on steel and aluminum.